Corporate sustainability and asset pricing models: empirical evidence for the Brazilian stock market - Vitor Gonçalves de Azevedo; André Alves Portela Santos; Lucila Maria de Souza Campos (Production)
Abstract The paper investigates the impact of corporate sustainability on asset prices. For that purpose, we develop a novel corporate sustainability factor and test the extent to which this factor is priced in an augmented four-factor version of the traditional Fama & French (1993) asset pricing model. The corporate sustainability factor is based on a zero-investment portfolio which is long in stocks with high sustainability and short in stocks with low sustainability. We use data on the Brazilian stock market to estimate alternative model specifications with different combinations of four explanatory variables: the corporate sustainability premium, the market risk factor premium, the size factor premium and the book-to-market factor premium. Our results indicate that corporate sustainability is priced and helps to explain the variability in the cross-section of expected stock returns.